Brain-Generated 17β-Estradiol Modulates Long-Term Synaptic Plasticity in the Primary Auditory Cortex of Adult Male Rats. (9th October 2021) - Soutar, Chloe N; Grenier, Patrick; Patel, Ashutosh; Kabitsis, Pauline P; Olmstead, Mary C; Bailey, Craig D C; Dringenberg, Hans C
Abstract: Neuron-derived 17β-estradiol (E2) alters synaptic transmission and plasticity in brain regions with endocrine and non-endocrine functions. Investigations into a modulatory role of E2 in synaptic activity and plasticity have mainly focused on the rodent hippocampal formation. In songbirds, E2 is synthesized by auditory forebrain neurons and promotes auditory signal processing and memory for salient acoustic stimuli; however, the modulatory effects of E2 on memory-related synaptic plasticity mechanisms have not been directly examined in the auditory forebrain. We investigated the effects of bidirectional E2 manipulations on synaptic transmission and long-term potentiation (LTP) in the rat primary auditory cortex (A1). Immunohistochemistry revealed widespread neuronal expression of the E2 biosynthetic enzyme aromatase in multiple regions of the rat sensory and association neocortex, including A1. In A1, E2 application reduced the threshold for in vivo LTP induction at layer IV synapses, whereas pharmacological suppression of E2 production by aromatase inhibition abolished LTP induction at layer II/III synapses. In acute A1 slices, glutamate and γ-aminobutyric acid (GABA) receptor-mediated currents were sensitive to E2 manipulations in a layer-specific manner. These findings demonstrate that locally synthesized E2 modulates synaptic transmission and plasticity in A1 and suggest potential mechanisms by which E2 contributes to auditory signal processing and memory.